Penal Mediation as a Medical Dispute Settlement for Hospital Malpractice Cases in Indonesia - Sirman Dahwal; Zico Junius Fernando; Ria Anggraeni Utami (Jurnal Ilmiah Kebijakan Hukum, 2022)
Penal Mediation is an alternative form of case settlement that originates with the idea of restorative justice. Seeing a large number of medical personnel being convicted in malpractice cases (primum remedium), mediation in dispute settlement for malpractice cases in hospitals becomes the concept of victim protection, harmonization, and overcoming rigidity/ formality in the applicable system. Therefore, the purpose of this study is to find solutions to avoid the adverse effects of the Criminal Justice System with the concept of mediation as an effort to resolve malpractice cases in the future. This paper used normative legal research or library research with a statute, conceptual, and comparative approach. The nature of the research used in this study is descriptive-prescriptive. The author used content analysis. The findings of this study are meant to provide an alternative solution to punishment which should be a last resort (ultimum remedium) from law enforcement in the form of non-litigation settlement through mediation.